MADRASAH ERA DIGITAL,: ANALISIS WACANA KEBIJAKAN PENDIDIKAN MADRASAH ERA DIGITAL - Abdurrohman, Asep -; Mas'ud, Muhammad -; -, Zulkifli - (Universitas Islam Syekh-Yusuf, 2021)
This research uses literature study with various data obtained by the author. Both primary data related to policies and secondary data. The results show that digital era madrasas need attention from policy makers, in this case the Ministry of Religion. The Ministry of Religion has a big responsibility in rearranging Madrasa policies in the digital era. Among the discourses and issues of madrasa policy include: mapping the opportunities and challenges of madrasas, reorienting the vision and mission of teachers, competent teachers, facilities and infrastructure,Management of Educational Components with a systems approach, and dual skill programs.